AB0522 GENDER DIFFERENCES IN GIANT CELLS ARTERITIS: ANALYSIS OF A MONOCENTRIC COHORT OF 100 PATIENTS. (2nd June 2020) - Regola, F.; Tincani, A.; Franceschini, F.; Toniati, P.
Abstract : Background: Giant Cells Arteritis (GCA) is the most common primary vasculitis in adults and usually occurs in patients older than 50 years. Epidemiological studies shown a higher prevalence of the disease in women compared to man. However, differences in clinical presentation between men and women have not been demonstrated, even if some distinctions have been suggested (1, 2). Objectives: The purpose of the present study is to analyze differences in the clinical presentation of GCA according to sex. Methods: We collected retrospectively clinical data of a monocentric cohort of 100 consecutive GCA patients. Mann Whitney test was used to compare continuous variables, while Chi-square test and Fisher's exact test were applied for comparison between qualitative variables. Results: One-hundred patients with a clinical diagnosis of GCA were enrolled in the study (68 women, 32 men). In all patients the diagnosis of vasculitis was histologically and/or radiologically confirmed. Main clinical data are reported in the table. Patients were classified according to vascular involvement in three groups: temporal arteritis (C-GCA), extracranial large vessel vasculitis (LV-GCA) and both cranial and extracranial vasculitis (LV-C-GCA). No significant differences in vascular distribution of the disease were found according to sex, even if large vessel involvement seems to be more frequent in women (43% vs 28%; p: ns). Male and female patients presented at diagnosis a similar clinical picture, with the same frequency of systemic symptoms (fever, fatigue, weight loss), polymyalgia rheumatica, visual symptoms and claudication. However, male patients complained more often temporal headache (90% vs 71%, p: 0.01), even no significant differences were found in the incidence of pathological findings at temporal artery physical examination (38% vs 32%; p: ns) and biopsy (59% vs 50%). On the contrary, in female patients a longer time to diagnosis was recorded (8 (2-49 vs 4 (0-35) months; p: 0.01). Conclusion: In our cohort of GCA patients, clinical presentation was similar in male and female patients, with no significant differences in clinical, radiological and laboratory findings. However, male patients presented more often temporal headache, the most typical symptom of GCA, and this could explain a shorter time to diagnosis, if compared to female. References: [1]Sturm A et al. Clin Exp Rheum, 2016 [2]Nir-Paz R et al. J of Rheum, 2002 Disclosure of Interests: None declared